Open sternoclavicular osteophyte debridement in the surgical management of sternoclavicular osteoarthritis: clinical outcome of a new procedure. (April 2022) - Ayekoloye, Charles I; Yin, Qi; Wood, Amanda; Frostick, Simon
Introduction: Symptomatic sternoclavicular osteoarthritis is uncommon but remains the most frequent non-traumatic condition affecting the sternoclavicular joint and tends to have a predilection for middle-aged women. It responds well to conservative management. Surgery is indicated when conservative management fails. We present the clinical outcome of open symptomatic sternoclavicular osteophyte debridement, a new operation for treating recalcitrant symptomatic sternoclavicular osteoarthritis. Methods: Five patients (five symptomatic sternoclavicular joints) with symptomatic sternoclavicular osteoarthritis underwent open sternoclavicular debridement following failure of conservative treatment. There were three females and two males. Mean age was 46.6 years (range 37.17–66). Four cases were primary osteoarthritis and one case was secondary to trauma. They were reviewed at mean follow-up at 35.4 months with minimum follow-up of 29 months. Assessment included Quick Disabilities of Arm Shoulder and Hand (DASH) and subjective patient satisfaction score. Results: There was no post-operative complication. Mean Quick DASH score 10.9 (range 0–29.5) at mean 35.4-month follow-up (range 29–43 months). Three patients reported excellent and two reported good outcome as per subjective satisfaction score. Conclusions: Open sternoclavicular debridement has proved to be a simple, safe and highly effective new surgical treatment for patients with symptomatic sternoclavicular osteoarthritis unresponsive to non-operative management.